(untitled) (Conferencea, 2022)
In this article, studies on the improvement of the RX regenerator used in the cleaning processes of cotton ginning enterprises have been carried out. The influence of the new working body proposed in the study - the number of drum plates with rubber plates - on the efficiency of cotton separation was studied, and the maximum level of separation efficiency was determined.